Monthly variations in growth pattern and condition factor of Periophthalmodon septemradiatus (Gobiiformes: Periophthalminae) living along the Bassac River in Viet Nam - Dinh, Quang Minh; Nguyen, Ton Huu Duc; Truong, Ngon Trong; Doan, Diep Xuan; Nguyen, Tien Thi Kieu (PeerJ, 2022)
Periophthalmodon septemradiatus (Hamilton, 1822) is a unique mudskipper living in the mudbanks from estuarine to riverine regions in the Vietnamese Mekong Delta (VMD), but there is no data on its growth patterns and condition factors that are helpful for fish resource assessment and adaptation understanding. This study was conducted at five sites, from the lower (Soc Trang province) to middle (Can Tho city) and upper (An Giang province) reaches of Bassac River in VMD, to provide knowledge on growth patterns and condition factors to this mudskippers. Fish samples were caught using traps and hands for 24 months, from July 2017 to June 2019, at these five sites. The total length and weight of 3,417 individuals (1,340 females and 2,077 males) varied by sex, season and site (p < 0.001 for all cases). This species exhibited a positive allometric type as the slope (b = 3.06 ± 0.01) of the length-weight relationship (LWR) was >3 (p < 0.001) for both sexes. The growth pattern changed with sex as mudskipper showed isometry in females but positive allometry in males. Maturity also affected fish growth type since it shifted from negative allometry in immature groups to positive allometry in mature groups. The growth pattern of fish changed from isometry in the dry season to positive allometry in the wet season. The mudskipper showed isometry at the lower reaches in Soc Trang but positive allometry at the middle and upper reaches in Can Tho and An Giang. The condition factor (CF) did not change according to sex, size and season, but with month and site variables. The present environmental condition in these studied sites tended to be not good enough for this fish as CF (0.95 ± 0.01) was less than 1 (p < 0.001). The findings provided basic information on the growth and adaptation of P. septemradiatus being helpful in fish adaptation understanding and resource conservation in VMD.
Keywords: Fish growth; Isometry; Length-weight relationship; Mekong Delta; Negative allometry; Regression parameters